Autofrettage of component-like ultra high Strength Steel Specimens with intersecting Holes - Fällgren Carl (EDP Sciences, 2021)
This work is primarily concerned with the fatigue life of high-pressure-bearing components with intersecting holes, typically used in Diesel engine fuel injection systems. The investigation focuses on specimens with intersecting holes that have undergone the process of Autofrettage (single mechanical overload), which is typically used to extend the fatigue life of components loaded by cyclic internal pressure. The resulting residual stress distribution thus influences the fatigue failure and especially the crack propagation behaviour of the components. In previous works, results showed that besides crack initiation, crack arrest behaviour has to be taken into account when calculating fatigue lives of autofrettaged specimens as the endurance limit is otherwise underestimated. In order to achieve reliable results, material testing with samples made of the ultra high strength steel W360 was performed. The resulting test data were used to simulate the Autofrettage process with finite-element analysis. Calculated residual stress distributions were used to determine at which levels of subsequent cyclic loading crack initiation would occur. For predicted crack initiation, the simulated residual stress distribution was used to investigate the crack propagation behaviour with fracture mechanics based approaches of different complexity in order to identify possible crack arrest or crack propagation. Calculated results were compared to experimental test data from component-like specimens. The comparison showed that the fracture mechanics based approaches are capable of describing the crack arrest and propagation behaviour reliably.